Eradicating Cultural Poverty In Sambas Regency Using A Partnership Model From The Perspective Of Islamic Development Economics - Purnamasari, Wulan; Refor Diansyah; Tari Indriani; Syukron Wahyudi; Resvan (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
The suboptimal state of economic development in Sambas Regency has resulted in the community living in cultural poverty, effectively sidelined amidst the abundance of natural resources in the region. Using the perspective of Islamic Development Economics, this study aims to formulate empowerment strategies that place justice and brotherhood as the main foundations for realising equitable and sustainable community welfare in Sambas Regency. The solution proposed is a Partnership Model for Community Economic Welfare Development that integrates the roles of the government, Sharia institutions, the private sector, and the community through the principles of Ta’awun and Syarikah. This model encompasses five strategic pillars: policy partnerships based on ukhuwah, Sharia investment and financing (mudharabah), expertise management (syarikah abdan), and collective entrepreneurship (syarikah al-inan). Through this synergy, it is hoped that an inclusive economic ecosystem will be created in Sambas Regency, where the community plays an active role as the primary agent in managing the region’s economic sovereignty in accordance with the principles of Maqashid al-Syariah.